(untitled) - Gold-Dworkin, Heidi (New York, NY., 2001)
The Little Scientists Hands-On Activities series of books is an outgrowth of the nationally acclaimed Little Scientists educational program. Like the popular scientific enrichment classes for which they are named, these books are designed to expose kids, ages 5 to 8, to the thrill of scientific discovery, while helping them to develop core scientific skills of deserving, critical thinking, communication, classifying, comparing, applying and generalizing, measuring, predicting, hypothesizing, and problem solving.
Keywords: Force and energy,Force and energy,Motion; Juvenile literature.,Experiments,Juvenile literature; Experiments